Downstream processing of high chain length polysialic acid using membrane adsorbers and clay minerals for application in tissue engineering. Issue 2 (1st October 2012) - Bice, Ismet; Celik, Hilal; Wolff, Christoph; Beutel, Sascha; Zahid, Maria; Hitzmann, Bernd; Rinas, Ursula; Kasper, Cornelia; Gerardy‐Schahn, Rita; Scheper, Thomas
<x xml:space="preserve">Abstract</x> Polysialic acid (polySia) is a carbohydrate polymer of varying chain length. It is a promising scaffold material for tissue engineering. In this work, high chain length polySia was produced by an Escherichia coli K1 strain in a 10‐L bioreactor in batch and fed‐batch mode, respectively. A new downstream process for polySia is presented, based on membrane adsorber technology and use of inorganic anion exchanger. These methods enable the replacement of precipitation steps, such as acetone, cetavlon, and ethanol precipitation of the already established purification process. The purification process was simplified, while process efficiency and product qualities were improved. The overall yield of polySia from a 10‐L batch cultivation process was 61% and for 10‐L fed‐batch cultivation process the yield was 40% with an overall purity of 98%. The endotoxin content was determined to be negligible (14 EU mg−1). The main advantage of this new downstream process is that polySia with high chain length of more than 130 degree of polymerization can be obtained. In fed‐batch cultivation, chain lengths up to 160 degree of polymerization were obtained.